NATIONAL STRUGGLE AS ONE OF THE TYPES OF PHYSICAL CULTURE - Shodi Bobomurodovich Umirov (American Journals, 2024)
The article provides an overview of the Uzbek national wrestling Quresh: the history of the development of kurash, as well as the rules for evaluating kurash competitions
Keywords: Kurash, wrestling, the art of wrestling, glasses, penalty points.